Pressure effects on electronic structure and magnetic properties of anisotropic metallic compounds - Grechnev, G.E.; Panfilov, A.S.; Fedorchenko, A.V.; Svechkarev, I.V.; FIlippov, V.B.; Lyashchenko, A.B.; Vasiliev, A.N. (Физика и техника высоких давлений, 2008)
Pressure effects on electronic structure and magnetic properties of anisotropic metallic materials (CrB₂, FeGe₂, LaFeAsO) are investigated. Magnetic susceptibilities of CrB₂ and FeGe₂ compounds were studied under hydrostatic pressure at fixed temperatures, 77 and 300 K. In order to analyze the experimental magnetovolume effects, the electronic structures were calculated ab initio in external magnetic field as a function of atomic volume by employing a full-potential LMTO method. The calculated field-induced magnetic moments and their volume derivatives compare favorably with the experimental pressure effects in magnetic properties of CrB₂ and FeGe₂. The main role of pressure in high-Tc superconductivity of LaFeAsO is found to reduce density of states at the Fermi level and to suppress ferromagnetic spin fluctuations.